Introduction to college chemistry - Wolfe, Drew H. (New York : McGraw-Hill, 1988)
"A comprehensive preparatory college chemistry textbook that can most effectively be used in beginning chemistry courses to prepare students for general college chemistry and in chemistry courses designed for nonscience students. Additionally, this book may be used in the first semester of some allied health chemistry courses. For this revised textbook, the author has added missing material, deleted superfluous material, rewritten passages to make them easier to understand, reorganized material within chapters to strengthen them and added features that make the book more interesting to the reader".
Includes bibliographical references.
English text.
Keywords: Chemistry